2008
DOI: 10.1038/ejhg.2008.214
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlations in Down syndrome identified by array CGH in 30 cases of partial trisomy and partial monosomy chromosome 21

Abstract: Down syndrome (DS) is one of the most frequent congenital birth defects, and the most common genetic cause of mental retardation. In most cases, DS results from the presence of an extra copy of chromosome 21. DS has a complex phenotype, and a major goal of DS research is to identify genotype -phenotype correlations. Cases of partial trisomy 21 and other HSA21 rearrangements associated with DS features could identify genomic regions associated with specific phenotypes. We have developed a BAC array spanning HSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
293
0
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(330 citation statements)
references
References 46 publications
26
293
0
11
Order By: Relevance
“…In agreement with Lyle et al, 2 we also found hemizygous deletions in a third region, from B36-37.5 Mb to the telomere, to be the most common abnormality (two from Cohort A, four from Cohort B, eight from DECIPHER, seven from Lyle et al). Also in agreement with Lyle et al, the phenotypes were relatively mild.…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with Lyle et al, 2 we also found hemizygous deletions in a third region, from B36-37.5 Mb to the telomere, to be the most common abnormality (two from Cohort A, four from Cohort B, eight from DECIPHER, seven from Lyle et al). Also in agreement with Lyle et al, the phenotypes were relatively mild.…”
Section: Discussionsupporting
confidence: 78%
“…This neglect has been attributed in part to the presumed global nature of the molecular and cellular abnormalities resulting from trisomy 21 (T21), which involves misexpression of hundreds of genes in every cell throughout life. Several "dosage-sensitive" regions, including genes and noncoding conserved elements, have been mapped across the length of Hsa21 and shown to be sufficient for induction of the complete phenotype of DS (Korbel et al, 2009;Lyle et al, 2009). Exciting new findings are demonstrating the considerable plasticity of the human genome, and, in addition to direct and indirect alteration of expression of Hsa21 and nonHsa21 genes, we have to consider that the variability of the DS phenotype may also be a result of copy number alteration of functional, nontraditional genomic elements.…”
Section: Gene Expression and Trisomy 21mentioning
confidence: 99%
“…The first from the centromere to 31.2 Mb contains 50 genes and produces severe phenotype [13]. The second from 31.2 to 36 Mb contain 80 genes but deletion is rare in this region indicating intolerance in monosomic state [13]. The third from 36-37.5 Mb to the telomere contain 130 genes and result into a milder phenotype [3,13].…”
Section: Discussionmentioning
confidence: 99%
“…Three broad regions are implicated to the phenotype of monosomy 21. The first from the centromere to 31.2 Mb contains 50 genes and produces severe phenotype [13]. The second from 31.2 to 36 Mb contain 80 genes but deletion is rare in this region indicating intolerance in monosomic state [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation